(Pseudo) sluicing in Preposition Stranding Contexts: The Case of Ta'izzi Arabic - Mustafa Ahmed Al-humari (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
The study explores the morphosyntactic properties of the elliptical structure of sluicing in Ta'izzi Arabic, a dialect spoken in the southwestern part of Yemen, with a particular focus on sluicing in preposition-stranding contexts within the generative grammar paradigm. The Arabic dialect under study seems to allow sluicing with preposition stranding, thus constituting, in principle, counterevidence to Preposition Stranding Generalization (PSG) proposed by Merchant (2001). That is, Arabic permits a preposition to be stranded under sluicing, though this is not allowed in regular wh-movements. The paper demonstrates that what gives the impression of sluicing in P-stranding contexts is actually pseudosluicing. Such a structure is not generated from a typical wh-question. Instead, it is originally derived from a wh-cleft source in which the relative clause containing the preposition and the copular pronoun are elided. This suggests that the language has two potential elliptical structures: true sluicing, which originates from regular wh-questions and TP ellipsis at PF, and pseudosluicing, which stems from a wh-cleft source where the ellipsis of the relative clause containing the preposition and the copular pronoun occurred at PF. It also suggests that, despite their distinct origins, the two elliptical derivations can be straightforwardly derived through the movement of the remnant wh-phrase from the specifier position of TP (Spec; TP) to the specifier position of CP (Spec; CP) in the sluiced clause.